Tailored indium sulfide-based materials for solar-energy conversion and utilization - Zhang, Jingjing; Wang, Hou; Yuan, Xingzhong; Zeng, Guangming; Tu, Wenguang; Wang, Sibo (Journal of photochemistry and photobiology. C, Photochemistry reviews, 2019)
Due to the defect structure, suitable band gap, photoelectric sensitivity and low toxicity, state-of-the-art accomplishments of In2S3-based photocatalysis and photovoltaics have been achieved for solar-energy conversion and utilization. A broad photoconversion field of photochemically environmental decontamination, artificial photosynthesis for renewable fuels, and solar cells makes sense for energy and environmental issues. [Display omitted] •The physico-chemical characteristics and properties of indium sulfide were discussed.•Synthesized strategies of In2S3-based materials were reviewed.•Recent progresses in In2S3-based environmental decontamination, artificial photosynthesis and solar cells were summarized.•Possible challenges in In2S3-based solar-energy conversion and utilization were proposed. To relieve the growing pressure originated from the energy shortage and environmental issues, solar-energy conversion into chemical or electrical energy has undergone an unprecedented development as a promising strategy in recent years. Indium sulfide (In2S3), an efficient visible-light harvester, has been extensively investigated in the field of photoconversion, owing to the fascinating merits including superior photo-absorption coefficient, photoelectric sensitivity, favorable carrier mobility, moderate band gap, excellent stability, and low toxicity. To take full advantage of these properties and further expand beyond the existing short board like low quantum efficiency, various In2S3-based functional nanostructures like nanoparticles, nanotubes, atomic two-dimensional sheets, and nanosheets-assembled complexes have been developed. Meanwhile, pleasurable characters of In2S3 have been modulated via defective engineering, doping, and hybridization (with inorganic materials or bio-molecules). Gratifyingly, In2S3-based photocatalytic, photoelectrocatalytic and photovoltaic systems have made significant impact on the field of energy and environmental issues. Therefore, this review provides an overview of crystal and morphologic structures of pristine In2S3 as well as many outstanding properties. Moreover, the pristine In2S3 and its derivatives with diverse synthesis routes are systematically summarized. Further, the advancement of In2S3-based photocatalytic, photoelectrocatalytic and photovoltaic systems, especially in environmental decontamination, artificial photosynthesis for renewable fuels and solar cells, are highlighted in detail. Ultimately, we conclude with a summary and propose some invigorating perspectives on the challenges from atomic (or macroscopical) structure modulation in material nature, photochemical behavior understanding to solar photovoltaic applications at the forefront of this research platform.